Freestanding NiFe Oxyfluoride Holey Film with Ultrahigh Volumetric Capacitance for Flexible Asymmetric Supercapacitors. Issue 3 (14th November 2017) - Liang, Kun; Marcus, Kyle; Yang, Zhenzhong; Zhou, Le; Pan, Hao; Bai, Yuanli; Du, Yingge; Engelhard, Mark H.; Yang, Yang
Abstract: In this work, a freestanding NiFe oxyfluoride (NiFeOF) holey film is prepared by electrochemical deposition and anodic treatments. With the combination of good electrical conductivity and holey structure, the NiFeOF holey film offers superior electrochemical performance with maximum specific capacitance of 670 F cm −3 (134 mF cm −2 ), due to the following reasons: (i) The residual metal alloy framework can be used as the current collector to improve electrode conductivity. Moreover, the as‐prepared freestanding NiFeOF holey film can be used as a supercapacitor electrode without reliance on binders and other additives. The residual metal alloy framework and binder‐free electrode effectively reduce electrode resistance, thus improving electron transport. (ii) The highly interconnected holey structure and hierarchical pore distribution provide a high specific surface area to improve electron transport, enhancing rapid ion transport, and mitigating diffusion limitations throughout the holey film. (iii) The excellent mechanical characteristics facilitate flexibility and cyclability related performance. Additionally, the NiFeOF holey film presents exceptional electrochemical performance, showing that it is a promising alternative for small/microsize electronic devices. Abstract : A freestanding NiFe oxyfluoride (NiFeOF) holey film is prepared by electrochemical deposition and anodic treatments. With the combination of good electrical conductivity and holey structure, the NiFeOF holey film presents exceptional electrochemical performance with maximum specific capacitance of 670 F cm −3 (134 mF cm −2 ), showing that it is a promising alternative for small/microsize electronic devices.